Performances em Hamlet: textualidades, teatralidades e liminaridades - Barros , Edlúcia Robélia Oliveira de (2015)
This dissertation is the result of a diverse literature and aims to analyze multiple aspects in the tragedy Hamlet, Prince of Denmark (1600-1601), the Englishman William Shakespeare (1564-1616), as a performative text. To do so, it establishes relationships between this tragedy and some issues discussed on performance studies, specifically theatricality, liminality and textuality. Hamlet’s story is first related to the concept of theatricality as state from the Russian playwright and theater director Nicolas Evreinov (1879-1953), as well as establishes dialogues with the notion of liminality discussed by folklorist and ethnographer Arnold van Gennep German (1873-1957), also with ideas of the Russian thinker Mikhail Bakhtin (1895-1975) about the performance of language, among other notions about performing and human performance practices. Hamlet, the text, appears on the threshold between completeness and movement, between textuality and theatricality, between readings and cultures. It is described and further analyzed Hamlet assembly in Moscow Art Theatre (MAT), one of the famous readings and rewrites the Shakespearean tragedy. A scenic production, which features dialogues and confrontations between text and scene, between Aesthetics, between readings of the tragedy, which express themselves through the collisions between the directors of this performances, the actors and the spectators. Finally comes to aspects of reception of Hamlet.